Food Insecurity Among Formerly Incarcerated Adults. (October 2019) - Testa, Alexander; Jackson, Dylan B.
The purpose of this study is to further the understanding of the hardships faced by formerly incarcerated individuals by investigating the association between prior incarceration and postrelease food insecurity. Drawing on data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), our findings demonstrate that a history of incarceration is associated with an increased likelihood of experiencing food insecurity. This association is found to partially operate through household income, depressive symptoms, marital status, and social isolation. Given the importance of food insecurity in predicting future health outcomes and nutritional behavior, food insecurity may be an important factor in driving health disparities among formerly incarcerated persons.